Architecture mode, sedimentary evolution and controlling factors of deepwater turbidity channels: A case study of the M Oilfield in West Africa - Wen-Biao Zhang (KeAi Communications Co., Ltd., 2017)
Abstract Turbidity channels have been considered as one of the important types of deepwater reservoir, and the study of their architecture plays a key role in efficient development of an oil field. To better understand the reservoir architecture of the lower Congo Basin M oilfield, semi-quantitative–quantitative study on turbidity channel depositional architecture patterns in the middle to lower slopes was conducted with the aid of abundant high quality materials (core, outcrop, logging and seismic data), employing seismic stratigraphy, seismic sedimentology and sedimentary petrography methods. Then, its sedimentary evolution was analyzed accordingly. The results indicated that in the study area, grade 3 to grade 5 architecture units were single channel, complex channel and channel systems, respectively. Single channel sinuosity is negatively correlated with the slope, as internal grains became finer and thickness became thinner from bottom to top, axis to edge. The migration type of a single channel within one complex channel can be lateral migration and along paleocurrent migration horizontally, and lateral, indented and swing stacking in section view. Based on external morphological characteristics and boundaries, channel systems are comprised of a weakly confining type and a non-confining type. The O73 channel system can be divided into four complex channels named S1–S4, from bottom to top, with gradually less incision and more accretion. The study in this article will promote deeper understanding of turbidity channel theory, guide 3D geological modeling in reservoir development and contribute to efficient development of such reservoirs.